Effect of Loading Rate on Fracture Behaviour and Shear Lips Formation of Al6061 Alloy - Harimon, Mohd Azhar; Najaf, Mohamad Ezaldeen; Abdul Latif, Noradila (Journal of Advanced Mechanical Engineering Applications, 2022)
Aluminium alloys are widely used in many engineering industries due to their mechanical and material properties. It is used in many applications, especially in automotive parts, like automobile cylinder heads, engine blocks, and chassis. It is important to obtain the behaviour of fracture of this material. Several materials testing has been conducted on aluminium 6061 alloy to fulfil the requirement in industries. However, the effect of specimen thickness on shear lip ratio and plastic zone size on fracture specimens for aluminium 6061 under the three-point bending test is hardly studied. Also, the fracture behaviour of this material has been not always clarified. This investigation’s primary goal is to study the effect of the thickness of the sample as well as the loading rate on the formation of shear lips for aluminium 6061. To find out whether shear lips occur on the fracture surface of aluminium 6061, a three-point bending test was performed on a Single Edge Notched Bending (SENB) specimen. Analysis has been made to determine the shear lips ratio dependence on specimen thickness and loading rate. Based on the result of the analysis, the shear lips ratio is decreasing as the thickness of the specimen increases. Besides that, the shear lips ratio is decreasing as the loading rates increases. A high loading rate and specimen thickness gave a result in low plasticity behaviour because the stress states are in plane strain conditions where the formation of shear lips is minimum. From the three-point bending test, a good agreement of data gains from the dependency of shear lips ratio on specimen thickness and loading rates. Overall, aluminium 6061 is fractured in a ductile manner with significant shear lips formation.